Police CrimeStat - Oberio, Elnelyn C.; Jamandre, Markh B. (Philippine Social Science Journal, 2020)
This project aimed to automate the manual entry of the incident reports of the Philippine National Police. The system is projected to provide effective monitoring and updated statistical reports that will be used for decision-making processes. All police stations within the designated area will have an installed application that is centralized nationwide. Thus, data analysis would be easier and useful for law enforcement agencies for long-term crime bust programs. The system has the following specific objectives: first is to provide easier access to blotter reports, to improve decision making with interactive maps, to promote information sharing, and lastly, to offer statistical information of incidents. Evaluation of incident reports by an authorized officer is necessary before encoding them into the system. The data that the system needs includes the following: complainant and suspect’s name(s), case details, and the type of offense. Inputted incident reports can be seen by the central office and other police stations; however, data manipulation is accessed only in the central office. The system can search and display case details in a printable format based on the user’s specified query. By utilizing the Google map application program interface (API), the user can quickly locate and see the crime’s exact location. This particular feature is challenging because there is a need to structure a detailed data mining design to promptly generate reliable reports. Once data are encoded in the system, the central office can create reports according to their needs. The system development started with data gathering by interviewing the Non-Uniform Personnel of Murcia Police station and performed the requirements analysis for the system.